A study on Flame Characteristics Premixed Burning by Giving Magnetic Field Induction - Deny tomy andrianto; Muh. Nurkoyim Kustanto; Yuni Hermawan; Nasrul Ilminnafik; Salahuddin Junus (Politeknik Negeri Lhokseumawe, 2023)
This study aims to compare the effect of magnetic field induction on the characteristics of the fire resulting from the combustion of premixed biodiesel calophyllum inophyllum . Further research on premixed combustion flames due to magnetic field induction. As time goes by, petroleum is currently running low, therefore alternative biofuels are needed. One type of non-food vegetable oil is Jatropha and calophyllum inophyllum oil, besides not being consumed, it can be processed into biodiesel as fuel. To get a more effective and efficient flame, you can apply a magnetic field effect to the fire, especially in terms of the burning rate of the fire. The experimental research method is to heat calophyllum inophyllum biodiesel until it is in the form of steam, then flow it to the burner which will then be given air which is controlled by the flow mass. Then the fire is ignited and the mass of the air flow is increased until the fire is lifted until it is extinguished. Two magnets are placed between the burners by varying the direction of the magnetic field N-S, N-N and the results of this study are the shape of the flame. The resulting fire is more transparent, clearer and more visible. The direction of the N-S magnetic field causes the temperature to be higher than the direction of the N-N magnetic field. The high and low of the flame is affected by the direction of the magnetic field, the stronger the N-S magnetic field. The magnetic field can affect the burning speed of the biodiesel flame. In a poor mixture (ϕ 1) in the presence of magnetic influence, the rate of fire is lower without the influence of a magnetic field, but in a rich mixture (ϕ 1) in the presence of a magnetic influence, the rate of fire is higher than without the influence of a magnetic field. This is due to the magnetic influence that induces oxygen. Oxygen is paramagnetic, so it can be attracted by magnetic fields.